2009
DOI: 10.1371/journal.pone.0008198
|View full text |Cite
|
Sign up to set email alerts
|

ActRIIA and BMPRII Type II BMP Receptor Subunits Selectively Required for Smad4-Independent BMP7-Evoked Chemotaxis

Abstract: Bone morphogenetic protein (BMP)-evoked reorientation and chemotaxis of cells occurs with rapid onset and involves events local to the cell membrane. The signaling pathways underlying these rapid processes likely diverge from those mediating classical transcriptional responses to BMPs but it remains unclear how BMP receptors are utilized to generate distinct intracellular mechanisms. We show that BMP7-evoked chemotaxis of monocytic cells depends on the activity of canonical type II BMP receptors. Although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 58 publications
(94 reference statements)
2
71
0
Order By: Relevance
“…To our knowledge, a role of Bmp7 in the regulation of neuronal migration has not been reported before. However, BMP7-mediated chemotactic and inhibitory functions in cell migration have been reported in other systems, including melanomas, osteoblasts and monocytic cell lines (Lee et al, 2006;Na et al, 2009;Perron and Dodd, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, a role of Bmp7 in the regulation of neuronal migration has not been reported before. However, BMP7-mediated chemotactic and inhibitory functions in cell migration have been reported in other systems, including melanomas, osteoblasts and monocytic cell lines (Lee et al, 2006;Na et al, 2009;Perron and Dodd, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…RNAi of Type II Receptors in Reporter Cells-The sequences of previously validated siRNAs against ACVR2B and BMPR2 were as described (34,35). On day 0, H-CrCR reporter cells were seeded in a 24-well plate (2.5 ϫ 10 4 /well).…”
Section: Expression Vectors and Lentivirus Production-full-lengthmentioning
confidence: 99%
“…Nodal signaling in utero is mediated by complexes of ACVR1B To directly assess the effects of different type II receptors on Nodal versus Nodal⅐Gdf1 signaling, we transfected H-CrCR reporter cells with established siRNAs (34,35). Depletion of 70% of ACVR2B mRNA in H-CrCR cells reduced the induction of CAGA-luc by recombinant Nodal to less than 30% (Fig.…”
Section: Heterodimerization Of Nodal With Gdf1 Allows Inhibition By Smentioning
confidence: 99%
“…Although originally reported as factors that induce bone and cartilage formation (3), BMPs have been shown to be critical for development (4)(5)(6). More recently, we and others have reported that BMPs regulate the immune system as BMP-6 inhibits B-and T-cell proliferation (7,8) and activates macrophages (9,10).…”
Section: Introductionmentioning
confidence: 99%